2022
DOI: 10.1037/pspp0000407
|View full text |Cite
|
Sign up to set email alerts
|

Positivity in peer perceptions over time: Personality explains variation at zero-acquaintance, popularity explains differential change.

Abstract: Positive peer perceptions over time: Personality explains variation at zeroacquaintance, popularity explains differential change. Journal of Personality and Social Psychology. Retrieved from https://psyarxiv.com/2gqf6/ Additional materials including data, R-Code, supplementary analyses, and a list of prior publications using data presented here are retrievable from https://osf.io/trb52/.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 46 publications
3
22
0
Order By: Relevance
“…Individual trajectories of meta-liking averages across the four measurement points in the interaction of 90 randomly selected participants. (Rau et al, 2022;Srivastava et al, 2010), showing that metaliking of adolescents displays a similar pattern. It appears that meta-liking is relatively stable within first social interactions, but there is room for adapting one's perception as new information becomes available.…”
Section: Figurementioning
confidence: 79%
See 1 more Smart Citation
“…Individual trajectories of meta-liking averages across the four measurement points in the interaction of 90 randomly selected participants. (Rau et al, 2022;Srivastava et al, 2010), showing that metaliking of adolescents displays a similar pattern. It appears that meta-liking is relatively stable within first social interactions, but there is room for adapting one's perception as new information becomes available.…”
Section: Figurementioning
confidence: 79%
“…The Role of Personality in Initial Meta-Liking and Changes in Meta-Liking A person's unique personality plays a central role in how they perceive themselves and others around them in social contexts (Back, Baumert, et al, 2011;Breil et al, 2019;Cuperman & Ickes, 2009;Rau et al, 2022). Tendencies to perceive their social environment, behave toward others, and feel about others give rise to certain expectations that people bring with them to social interactions.…”
Section: Changes In Meta-liking In Initial Social Interactionsmentioning
confidence: 99%
“…This could be done by using a two-step approach where SRM effects are extracted separately for each measurement time point and are then treated as observed variables in latent growth models or autoregressive models (cf. Rau et al, 2019; Rau et al, 2022) or by applying longitudinal social relations structural equation modeling (Nestler et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the study design and a comprehensive list of all measures can be found in the study codebook. Two investigations on different research topics have thus far also analyzed LeiCo data (Grosz et al, 2020; Rau et al, 2021). Only the measures that are relevant for the current research question will be described here.…”
Section: Methodsmentioning
confidence: 99%